Islamic administration: a quest for a basis - Wahiduzzaman, M
The author tries to explore the possibilities of having a discipline to be called Islamic administration for the simple reason that today the study of neither pure science nor social science is absolutely value free or objective. He discusses modern scientific reasoning and dialectical thinking and on basis of this the attempt is made to see how far Islam is a state of reason. Thus the paper attempts to establish a rational basis of Islamic administration and further explains that administration a secular science, can also have a kind of public administration to be called Islamic administration
Keywords: Islamic Administration; Public Administration